The Parameter Genetic of the generation crossed F4 Soybean Detam-2 and Grobogan - DIAH PUSPITA ANWAR; DIANA SOFIAH HANAFIAH; EVA SARTINI BAYU (Universitas Sumatera Utara, 2019)
The research aimed to get The Parameter genetic of the generation crossed F4 Soybean Detam-2 and Grobogan . The research was conducted at experimental field of college of Agriculture USU in March 2017 up to August 2017. The parameters observed were : the days of flowering, the time of harvested, the plant height, the number of primary branches,the number seeds per plant, the weight of 100 seeds. The result showed that there were nineteen sample of genotype that have the character of time early ripening and high production Soybean plant F4 each row of the best result of crossed.